Exposure to Child-Directed TV Advertising and Preschoolers’ Intake of Advertised Cereals - Emond, Jennifer A. (Am J Prev Med, 2018)
INTRODUCTION: Child-directed TV advertising is believed to influence children’s diets, yet prospective studies in naturalistic settings are absent. This study examined if child-directed TV advertisement exposure for ten brands of high-sugar breakfast cereals was associated with children’s intake of those brands prospectively. METHODS: Observational study of 624 preschool-age children and their parents conducted in New Hampshire, 2014–2015. Over 1 year, parents completed a baseline and six online follow-up surveys, one every 8 weeks. Children’s exposure to high-sugar breakfast cereal TV advertisements was based on the network-specific TV programs children watched in the 7 days prior to each follow-up assessment, and parents reported children’s intake of each advertised high-sugar breakfast cereal brand during that same 7 day period. Data were analyzed in 2017– 2018. RESULTS: In the fully adjusted Poisson regression model accounting for repeated measures and brand-specific effects, children with high-sugar breakfast cereal advertisement exposure in the past 7 days (i.e., recent exposure; RR=1.34, 95% CI=1.04, 1.72), at any assessment in the past (RR=1.23, 95% CI=1.06, 1.42) or recent and past exposure (RR=1.37, 95% CI=1.15, 1.63) combined had an increased risk of brand-specific high-sugar breakfast cereal intake. Absolute risk difference of children’s high-sugar breakfast cereal intake because of high-sugar breakfast cereal TV advertisement exposure varied by brand. CONCLUSIONS: This naturalistic study demonstrates that child-directed high-sugar breakfast cereal TV advertising was prospectively associated with brand-specific high-sugar breakfast cereal intake among preschoolers. Findings indicate that child-directed advertising influences begin earlier and last longer than previously demonstrated, highlighting limitations of current industry guidelines regarding the marketing of high-sugar foods to children under age 6 years.